2022
DOI: 10.3390/ijgi11100525
|View full text |Cite
|
Sign up to set email alerts
|

From Meadow to Map: Integrating Field Surveys and Interactive Visualizations for Invasive Species Management in a National Park

Abstract: Invasive species are an important and growing issue of concern for land managers, and the ability to collect and visualize species coverage data is vital to the management of invasive and native species. This is particularly true of spatial data, which provides invaluable information on location, establishment rates, and spread rates necessary for managing habitats. However, current methods of collection are rarely integrated into a full management tool, making it difficult to quickly collect and visualize mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This investigation addressed how intraspecific variation of tree species across ecosystems affected species classifications from imaging spectroscopy data, which is an important consideration in large-scale vegetation mapping. Implications of accurate vegetation species classifications across large geographic areas include developing baseline species distributions for tracking future range shifts [5][6][7], identifying locations where rare species exist [1], and monitoring invasive species [2][3][4]. Here we demonstrated that despite the high intra-specific variability of M. polymorpha across ecosystems, accurate classifications of this species were possible.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This investigation addressed how intraspecific variation of tree species across ecosystems affected species classifications from imaging spectroscopy data, which is an important consideration in large-scale vegetation mapping. Implications of accurate vegetation species classifications across large geographic areas include developing baseline species distributions for tracking future range shifts [5][6][7], identifying locations where rare species exist [1], and monitoring invasive species [2][3][4]. Here we demonstrated that despite the high intra-specific variability of M. polymorpha across ecosystems, accurate classifications of this species were possible.…”
Section: Discussionmentioning
confidence: 84%
“…Spatial information on tree species distributions has many conservation applications including monitoring keystone or endangered species [1], invasive species tracking [2][3][4], and modeling climate change outcomes [5][6][7], among others. Remote sensing data are increasingly being used to circumvent the limitations of traditional field-based forest inventories.…”
Section: Introductionmentioning
confidence: 99%
“…GIS models for slums development and planning are usually created using ESRI ModelBuilder which is an ArcGIS application to generate, edit, and analyze models (Alzahrani, 2022). Model Builder introduces graphical user interface, which makes it easier to design, visualize, edit, and carry out geoprocessing workflows, as well as to publish and use outputs across various geographic contexts (Randall et al, 2022).…”
Section: Land Suitability Analysis For Slums Relocation Site Selectionmentioning
confidence: 99%